Beneficios de la Pueraria phaseoloides, como cobertura del suelo en el cultivo de Palma Aceitera (Elaeis guineensis) en el Ecuador - Tirape Hidalgo, Gilda Jackeline (2022)
The benefits of P. phaseoloides as soil cover in the cultivation of Oil Palm (Elaeis guineensis), in Ecuador, we can mention that current intensive agriculture is degrading the soil, due to the misuse of pesticides that contaminate water and air. The information presented is based on techniques of synthesis, analysis and summary of the aforementioned topic, managing to seek awareness in the producers dedicated to the cultivation of Palm. P. phaseoloides increases fertility and competition for weeds in soils containing nitrogen, calcium, and magnesium. The number of weed species disappears due to the establishment of the vegetal cover of P. phaseoloides, being a profitable method, it has great advantages such as reducing the excessive use of chemical products that are harmful to the environment. The use of P. phaseoloides as soil cover in African palm in Ecuador is an alternative method for soil protection and this method also has benefits such as irrigation management, being sustainable for small and large producers, lowering costs of the management that is carried out in the cultivation of Palm Oil.